Analysis of Spontaneous Ignition Temperature and Flash Point for Predicting Fire Risk in Biomass Fuel Pellet Storage - Dušan Bóna; Daniel Chovanec; Jana Jaďuďová; Linda Makovická Osvaldová; Iveta Marková (BioResources)
Biomass pellet fuel is one of the alternative renewable energy sources, which has an important place in the fuel market. This article analyses the spontaneous ignition temperature and flash point temperature, which are the most important characteristics for fire risk prediction, especially in the storage. The Norway spruce pellet and experimental pellet with digestate sawdust were tested according to ISO 871: 2010. The novelty of this research is the application of the Setchin Furnace test. The spontaneous ignition temperature for the Norway spruce pellet and the experimental pellet were established as 420 and 450 °C, respectively. The flash point temperature for the Norway spruce pellet was 330 °C and for the experimental pellet 320 °C. The activation energy was higher for the Norway spruce pellet (65.4 KJ.mol-1) for spontaneous ignition temperature and for the experimental pellet (42.1 KJ.mol-1) for flash point temperature.